Report of the Committee on Economic Education - Walstad, William (American Economic Review, 2006)
The CEE sponsored three paper sessions as part of the AEA program at the 2006 ASSA annual meetings. The first focused on “Research on Teaching Innovations.” It was organized by Paul Romer and chaired by Charles Ballard. The paper by Susan Pozo and Charles Stull studies the results of a required mathematics unit on students’ overall class performance. The second paper, by Sheryl Ball, Catherine Eckel, and Christian Rojas, reports the results of a controlled experiment testing the effectiveness of the Wireless Interactive Teaching System (WITS) at Virginia Tech. The third paper, by Wayne Grove and Tim Wasserman, reports results in cognitive achievement gains in an introductory economics course by assigning graded problem sets. The session discussants were Julian Betts, Frank Levy, and Michael Murray. The three papers are published in this issue of the Papers and Proceedings. The second CEE paper session centered on “Research on Ph.D. Programs in Economics.” It was organized by Wendy Stock and chaired by Alan Krueger. The paper by T. Aldrich Finegan and John Siegfried analyzed Americans who were admitted to Ph.D. programs in economics, but who did not enroll. The second paper, by T. Aldrich Finegan and Wendy Stock, investigated attrition in doctoral programs in economics. The third paper, by Wendy Stock and John Siegfried, examined elapsed time from entry into a Ph.D. program to completion of the degree for the class of 2001–2002. The session discussants were Jeffrey A. Groen, Robert E. Hall, Richard Freeman, and Alan Krueger. The three papers are also published in this issue of the Papers and Proceedings. Michael Watts organized and chaired the third session on “Teaching and Testing in Undergraduate Economics.” The paper by Michael Watts and William Becker reports new evidence on whether classroom practices have changed over the past decade and in different types of economics courses and institutions. The paper by KimMarie McGoldrick investigates the degree to which institutions have responded to the Siegfried et al. (1991) recommendations that every student be required to “do economics.” The paper by William Walstad and Michael Watts reports on the test development and preliminary results of the fourth edition of the Test of Understanding of College Economics (TUCE). The paper by Paul Grimes, Jane Lopus, Rodney Pearson, and William Becker examines the effects of mandated human subjects protocols on the amount of research in economic education. Charles Holt, John Siegfried, Theodore Bergstrom, and Claudia Parliament served as discussants for the session. The Committee continues to believe that workshops on teaching provide a valuable service to association members. So, for the tenth year, the Committee sponsored a one-day workshop as part of the AEA program at the 2006 ASSA annual meetings. The first workshop session, “Teaching Introductory Microeconomics,” was organized and chaired by Daniel Hamermesh. It featured presentations from Kenneth Elzinga, Daniel Hamermesh, and G. Dirk Mateer, all of whom have substantial and varied experience in teaching introductory microeconomics at different universities. The second workshop session was devoted to the ongoing Teaching Innovations Program (TIP) for economics instructors, which is described later in this report. The workshop was organized and chaired by Michael Salemi, and presentations where made by Gail Hoyt, Mark Maier, KimMarie McGoldrick, Michael Salemi, and William Walstad. The session described the activity of the participants in the 2005 workshops and explained the instructional content, likely experience, and benefits for economic faculty members who enroll and participate in the TIP during 2006. The third workshop was a poster session organized and directed by Rae Jean Goodman. It included 14 poster contributions on teaching ideas and projects for the undergraduate economics curriculum: (1) using creativity in assessment to teach economics (Mary Ellen Mallia); (2) techniques and effectiveness of interactive classroom instruction software (Michele T. Villinski); (3) using surveys to teach economic concepts (Kirsten K. Madden); (4) using personal response system clickers in principles (Martin Milkman and Barry